Association between Bioelectrical Impedance Parameters, Magnetic Resonance Imaging Muscle Parameters, and Fatty Liver Severity in Children and Adolescents - Kyungchul Song; Eun Gyung Seol; Eunju Lee; Hye Sun Lee; Hana Lee; Hyun Wook Chae; Hyun Joo Shin (Gut and Liver)
Background/Aims: To evaluate the associations between pediatric fatty liver severity, bioelectrical impedance analysis (BIA), and magnetic resonance imaging parameters, including total psoas muscle surface area (tPMSA) and paraspinal muscle fat (PMF). Methods: Children and adolescents who underwent BIA and liver magnetic resonance imaging between September 2022 and November 2023 were included. Linear regression analyses identified predictors of liver proton density fat fraction (PDFF) including BIA parameters, tPMSA, and PMF. Ordinal logistic regression analysis identified the association between these parameters and fatty liver grades. Pearson’s correlation coefficients were used to evaluate the relationships between tPMSA and muscle-related BIA parameters, and between PMF and fat-related BIA parameters. Results: Overall, 74 participants aged 8 to 16 years were included in the study. In the linear regression analyses, the percentage of body fat was positively associated with PDFF in all participants, whereas muscle-related BIA parameters were negatively associated with PDFF in participants with obesity. PMF and the PMF index were positively associated with PDFF in normalweight and overweight participants. In the ordinal logistic regression, percentage of body fat was positively associated with fatty liver grade in normal-weight and overweight participants and those with obesity, whereas muscle-related BIA parameters were negatively associated with fatty liver grade in participants with obesity. The PMF index was positively associated with fatty liver grade in normal/overweight participants. In the Pearson correlation analysis, muscle-related BIA parameters were correlated with tPMSA, and the fat-related BIA parameters were correlated with PMF. Conclusions: BIA parameters and PMF are potential screening tools for assessing fatty liver in children.